A comparison of accuracy and safety between stem-first and cup-first total hip arthroplasty: a prospective randomised controlled trial. Issue 2 (March 2023) - Iwakiri, Kentaro; Ohta, Yoichi; Minoda, Yukihide; Kobayashi, Akio; Nakamura, Hiroaki
Background: The combined anteversion theory to prevent impingement in total hip arthroplasty (THA) has been proposed. However, because stem-anteversion is influenced by the native femoral anteversion and the stem flexion/extension angle, it is often difficult to adjust stem anteversion during surgery. Therefore, the stem-first (combined anteversion) technique may be useful to adjust and achieve appropriate cup anteversion during surgery with respect to the implanted stem anteversion angle. However, the technique may adversely affect cup or stem angle accuracy and result in intra-operative bleeding, post-operative adverse events, and prolonged operative time. It is inconclusive whether either the stem-first or cup-first technique is safe or accurate. Therefore, this study assessed the accuracy and safety of stem-first THA compared to those of cup-first THA. Materials and methods: This prospective randomised controlled trial analysed 114 patients who were randomly divided into 2 groups (stem-first group: n = 57, cup-first group (control group): n = 57). Primary outcomes included cup and stem angle, the discrepancies from the targeted angle and combined anteversion (evaluated via CT at 3 months postoperatively). Secondary outcomes included intraoperative blood loss, operative time, WOMAC, and adverse events. Results: There were no significant differences in age, gender, BMI or in the primary and secondary outcomes between the 2 groups. Conclusions: Performing stem-first in THA did not adversely affect cup and stem angle accuracy, or result in intraoperative bleeding, prolongation of operative time, or postoperative adverse events. Thus, performing stem-first may be advantageous for achieving combined anteversion theory. Trial registration: University Hospital Medical Information Network (UMIN) registration number UMIN000025189.